SISTEM PEMANTAUAN DAN KENDALI KUALITAS AIR BERBASIS ARDUINO CLOUD - Hidayati, Rahmi; Ikhsan, Afif Muhammad; Nirmala, Irma (UNIVERSITAS STEKOM, 2024)
Fish farmers often face the problem of difficulty monitoring water quality from time to time. One method that can make it easier for fish farmers is to develop a system using the forward chaining method. This research aims to make it easier for fish farmers to monitor and control water quality automatically. This system can monitor and control automatically based on facts collected. Things to pay attention to in the system are the suitability level of temperature, pH, and turbidity in the water. The monitoring and control system using the forward chaining method functions 100% by the rules that have been fully implemented